A Study on Second Harmonic Excitation in Electron Beam–Plasma Instability - Rafiei, Maryamsadat; Sahrai, Mostafa; Hosseinpour, Mahboub; Esfandyari-Kalejahi, Abdolrasoul (Frontiers in Astronomy and Space Sciences, 2022)
The electron beam–plasma interaction is a fundamental nonlinear plasma process that is frequently taking place in space and laboratory plasmas. Such an interaction is found to generate electromagnetic waves observed in space plasmas. Using the two-dimensional electromagnetic particle in cell simulations, we investigated the second harmonic excitation in the electron beam–plasma instability. Results showed that, first, the Langmuir waves are excited in the system; then at longer time scales, following the excitation of ion acoustic waves, the second harmonic electromagnetic waves are excited. We found that in the case of background pair plasmas, where the masses are the same, there is no signature of waves in the second harmonic, which is a direct verification of the three-wave coupling mechanism for the generation of electromagnetic waves in the second harmonic.